Public relations and the power of creativity : strategic opportunities, innovation and critical challenges - Roberts-Bowman, Sarah, 1965-; Crookes, Adrian; Romenti, Stefania; Ihlen, Øyvind (Advances in public relations and communication management,, 2018)
Creativity is the development and use of imagination to solve current challenges or create innovative ideas for the future. The complexity and challenges of the contemporary world arguably require increasing levels of creativity and innovation to manage the disruptive forces at work and build a prosperous and sustainable global society. Public relations isoften seen as the discipline that amplifies creative ideas developed by othersectors, but this is changing. With the blurring of lines among creativeindustries, organisations are increasingly turning to PR to generate the 'big ideas' at the heart of effective communication. This volume gathers 12 outstanding contributions from scholarsbased in Germany, Finland, Austria, Romania, the UK, Spain, France, Norway,Turkey and the USA. Taken together, the chapters demonstrate a range of possibilities for creative thinking about public relations management and collaboration in different settings and with different purposes. The chapters hint at opportunities, point towards innovation, and challenge our thinking about the power of creativity.